Deciphering the enigma: the role of Philosophy in Kant and Schopenhauer - Gomez N. Pereira, Rafael (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The aim of this essay is to analyze the role of philosophy based on the interplay between Immanuel Kant and Arthur Schopenhauer. Considering the intellectual connection between these philosophers, we intend to look at the relevance and the importance of philosophical knowledge for each of them, searching for alignments and differences concerning the role that philosophy should play in structuring the intellect. On Kant's theories, we argue that philosophy is the preliminary path to control of pure reason, presenting the individuals the limits and possibilities of rational knowledge. On Schopenhauer's side, our intention was to suggest that, beyond rationality, there would be a metaphysical instance marked by the Will as something irrational, and that philosophy would be responsible for contemplating this same Will through the Idea.